Barcelona's housing policy under austerity urbanism: a contribution to the debate on degrowth and urban planning. Issue 4 (3rd April 2022) - Martínez Alonso, Laura
ABSTRACT: The housing policy of Barcelona, the Plan for the Right to Housing (2015–2020), implemented by the anti-austerity local government of Barcelona en Comú, relates closely to degrowth imaginaries and norms. It incorporates vacant housing to the public housing stock, develops a special unit for attending evictions and other residential emergencies, and introduces support for promising yet marginal tenure forms such as co-housing or leasehold estate. However, a critical analysis of this policy reveals strong contradictions and limitations. Given the existing uneven socio-spatial dynamics of a global city such as Barcelona, the well-established power relations in the production of urban space, and the still-dominant discourse of austerity, the local government's actions remain precarious. However, albeit both promising and contradictory, Barcelona's housing policy proves to be a useful case for developing degrowth planning principles and tools for urban housing policy and beyond.